2018
DOI: 10.1111/ene.13548
|View full text |Cite
|
Sign up to set email alerts
|

Potential indications for deep brain stimulation in neurological disorders: an evolving field

Abstract: Deep brain stimulation (DBS) is an established therapy for appropriately selected patients with movement disorders and neuropsychiatric conditions. Although the exact mechanisms and biology of DBS are not fully understood, it is a safe and well-tolerated therapy for many refractory cases of neuropsychiatric disease. Increasingly, DBS has been explored in other conditions with encouraging results. In this paper, available data is reviewed and new DBS targets, challenges and future directions in neurological dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 66 publications
0
16
0
1
Order By: Relevance
“…Neurosurgical experience and advances would support lowering intervention thresholds. Safety data from a wealth of procedures with an indwelling lead/cannula-such as deep brain stimulation (DBS) where a number of anatomical locations, including deep structures, have been targeted-support the lower thresholds as a relatively low rate of serious adverse events are now reported (Budman et al, 2018). In line with DBS safety, striatal intraparenchymal fetal mesencephalic transplantation has demonstrated that the neurosurgical procedure itself is very safe (Lindvall, 2015).…”
Section: Safety Of Gflsmentioning
confidence: 99%
“…Neurosurgical experience and advances would support lowering intervention thresholds. Safety data from a wealth of procedures with an indwelling lead/cannula-such as deep brain stimulation (DBS) where a number of anatomical locations, including deep structures, have been targeted-support the lower thresholds as a relatively low rate of serious adverse events are now reported (Budman et al, 2018). In line with DBS safety, striatal intraparenchymal fetal mesencephalic transplantation has demonstrated that the neurosurgical procedure itself is very safe (Lindvall, 2015).…”
Section: Safety Of Gflsmentioning
confidence: 99%
“…At present, 28 cerebral targets are utilized in DBS according to this registry. These targets (inclusive of multiple sites being used to treat the same disorder) included: PD [nucleus basalis of Meynert, STN, GPi, ventral intermediate thalamic nucleus, pedunculopontine nucleus (PPN)], depression (subgenual cingulate gyrus, habenula, medial forebrain bundle, inferior thalamic peduncle, ventral capsule/ventral striatum, nucleus accumbens and anterior limb of the internal capsule;), and obsessive-compulsive disorder (medial thalamus, inferior thalamic peduncle, ventral capsule/ventral striatum, nucleus accumbens, anterior limb of the internal capsule, bed nucleus of the stria terminalis and the STN; Budman et al, 2018;Lee et al, 2019). Nearby targets for the same disorder often may be no more than a few millimeters apart.…”
Section: Emerging Dbs Targets In Non-motor Disordersmentioning
confidence: 99%
“…The positive value of novel neurotechnologies lies in their potential to improve dramatically the life prospects of many people. These include life-changing therapies for conditions like Parkinson’s disease, essential tremor, stroke, paralysis, Alzheimer’s disease and treatment-resistant depression (Budman et al, 2018; Lozano and Lipsman, 2013). People with paralysis or limb loss could use brain-controlled prosthetics to transcend their bodily limitations (Wood, 2017).…”
Section: Introductionmentioning
confidence: 99%